Эпоха великого переселения народов: Херсонес Таврический и варвары - Ушаков, С.В. (Археологический альманах, 2012)
The problem of co-operation of barbarism and civilization on the example of history of Taurica Chersonese in an epoch of Great migration of people is examined in the article. As a result of care of Romans from Chersonese and South-west Crimea a city appeared unsupported external force which played in I-III cc. key value for the survival of city, and now the new system of mutual relations lines up with neighboring barbarians. In city in late roman time building bits and pieces were saved only separate building. In the end of IV - to the middle of V cc. town wine production (in North and the Northeastern districts) stop the existence. Character of material culture changes on the whole, and the preliminary analysis of complexes of finds allows to conclude that economic connections of Chersonese are largely locked on the pool of the Black sea. Small Christian community of end of IV - V cc. began a new impulse in connection with the expedition of Capiton, and a Judaic synagogue reforms in a Christian temple - basilica of V c. with a pentahedral apse. Other Christian temples appear, morally, not early than in epoch of Justinian I. Within the framework of the most transitional period which lasted approximately to the middle of VI c., there is a relative succession of basic elements of culture. This transitional epoch and created terms for smooth “byzantinization” once one of the largest centers of ancient culture in black sea Region. To the middle of VI c. we have an original “puff pie” of ethnos and cultures on small territory of south-west part of peninsula.